Pengaruh Debt to Asset Ratio dan Total Asset Turnover terhadap Harga Saham pada PT Summarecon Agung Tbk Periode 2014-2023 - Nyayu Nurmalinda; Khayatun Nufus (LAP4B, 2025)
This study analyzes the effect of Debt to Asset Ratio (DAR) and Total Asset Turnover (TATO) on the share price of PT Summarecon Agung Tbk for the 2014-2023 period. Using a quantitative approach with secondary data from the company's financial statements, the analysis was carried out through multiple linear regression with SPSS version 26. The results of the partial test showed that DAR had no significant effect on the stock price (t-count = 0.204 < t-table = 2.365; sig. = 0.844 > 0.05), while TATO had a significant positive effect (t-count = 4.392 > t-table = 2.365; sig. = 0.003 < 0.05). Simultaneous tests produced a significant influence of both variables on stock prices (F-count = 9.654 > F-table = 4.737; sig. = 0.010 < 0.05). An Adjusted R² value of 65.8% indicates good model predictability, with a correlation coefficient of 0.857 indicating a very strong relationship. These findings confirm that asset use efficiency plays a greater role in determining stock prices than the company's debt structure.